2017
DOI: 10.1038/srep44578
|View full text |Cite
|
Sign up to set email alerts
|

Computationally Discovered Potentiating Role of Glycans on NMDA Receptors

Abstract: N-methyl-D-aspartate receptors (NMDARs) are glycoproteins in the brain central to learning and memory. The effects of glycosylation on the structure and dynamics of NMDARs are largely unknown. In this work, we use extensive molecular dynamics simulations of GluN1 and GluN2B ligand binding domains (LBDs) of NMDARs to investigate these effects. Our simulations predict that intra-domain interactions involving the glycan attached to residue GluN1-N440 stabilize closed-clamshell conformations of the GluN1 LBD. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(54 citation statements)
references
References 51 publications
1
52
1
Order By: Relevance
“…The N ‐glycosylation site at N440 is located in the upper lobe of the GluN1 LBD and was predicted to stabilize a closed LBD conformation (Sinitskiy et al . ) and mutation of this consensus site for glycosylation reduced NMDAR glycine affinity in functional studies. GluN1‐N440 is analogous to the GluK2‐N430 glycosylation site, which is one of three sites mutated in GluK2ΔNG.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The N ‐glycosylation site at N440 is located in the upper lobe of the GluN1 LBD and was predicted to stabilize a closed LBD conformation (Sinitskiy et al . ) and mutation of this consensus site for glycosylation reduced NMDAR glycine affinity in functional studies. GluN1‐N440 is analogous to the GluK2‐N430 glycosylation site, which is one of three sites mutated in GluK2ΔNG.…”
Section: Discussionmentioning
confidence: 96%
“…The opposite changes in desensitization kinetics that we observed with HNK‐1 conjugation to wild‐type and GluK2ΔNG KARs suggest that HNK‐1–receptor interactions in distinct functional domains differentially influence receptor gating, and modelling studies such as those performed with NMDAR subunits would be a useful approach for understanding these interactions (Sinitskiy et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, an empirical rule has been known in the community of specialists applying MSMs to study biomolecules, namely, that the slowest implicit timescale captured by an MSM can go up to the values on the same order of magnitude as the aggregate sampling achieved in the used MD dataset. In previous studies of specific biomolecular systems with MSMs based on MD simulations, reported longest implicit timescales turned out to be smaller than the aggregate sampling by at least one order of magnitude [5][6][7][8][9][10][11][12][13][14][15][16][17] or comparable to the aggregate sampling. [18][19][20][21][22] In this paper, we analyze several MSMs with different topologies to uncover the reasons for the above empirical rule.…”
Section: Introductionmentioning
confidence: 99%